Pass-through business entity choice and earnings management: evidence from UK real estate investment trust conversion - Liang, Jian; Dong, Zhi; Zheng, Mo (International Journal of Strategic Property Management, 2022)
This empirical study innovatively investigates how the choice of a pass-through business entity and corresponding regulatory regime influence firms’ earnings management (EM) behaviors by testing on the UK Real Estate Investment Trust (REIT) conversion. A substantial proportion of UK non-REIT publicly traded property companies (LPCs) have chosen to become REITs since the UK REITs were launched in 2007. We conduct a series of tests on a database containing UK LPCs and REITs from 2000 to 2019 and find that conversion into pass-through business entity regimes like REITs that enjoy more favorable tax treatment but face more restrictions leads to more accrual earnings management (AEM) activity, but less real earnings management (REM) activity.